Sakarya Havzası'nın Yüksek Çözünürlüklü Hidrolojik Modelinin Yapılandırılması - Yaykıran, Salim (Fen Bilimleri Enstitüsü, 2016)
Yeryüzündeki en önemli yaşam kaynağı olarak kabul edilen su, tüm canlılar için hayati önem taşımaktadır. Dünya nüfusundaki hızlı artış, sanayileşme ve tarımsal faaliyetler su kaynakları kullanımındaki artışı da beraberinde getirmiştir. Küresel ısınma ve iklim değişikliğinin potansiyel etkileri ile sorunlar daha da büyümekte, potansiyel su miktarı endişe duyulacak düzeye ulaşmakta; dolayısıyla su kaynaklarının bilinçli kullanımı daha da önemli hale gelmektedir. Türkiye; kişi başına düşen yıllık 1519 m3 su miktarı ile su sıkıntısı yaşayan ülkeler arasında yer almaktadır. Bu açıdan doğal su kaynaklarının korunması, geliştirilmesi ve sürdürülebilirliğin sağlanması amacıyla yapılacak çalışmalara önem ve öncelik verilmelidir. Ülkemizdeki su kaynaklarının havza bazında yönetimi, sürdürülebilir kalkınmanın temelini oluşturmakta ve Avrupa Birliği Su Çerçeve Direktifi hedeflerine ulaşılmasında, bütünleşik havza yönetimi temel araç olarak kabul edilmektedir. Ülkemizde yer alan 25 nehir havzasından biri olan Sakarya Havzası, Anadolu Yarımadası'nın kuzeybatısında yer almaktadır. Havza; 58160 km2'lik drenaj alanı ile Türkiye'nin yaklaşık %7'sini kaplamaktadır. Ankara ve İstanbul gibi büyük merkezler arasında yer alması sebebiyle; su transferleri, ekonomik, kültürel faaliyetler ve ulaşım açısından önem arz etmektedir. Havza; kişi başına düşen yıllık 1000 – 1700 m3 arasında değişen su miktarı nedeniyle, su sıkıntısı çeken havzalar sınıfında yer almaktadır. Nüfus artışı, iklimsel değişimler ve uygun su yönetiminin sağlanamaması gibi sorunlar nedeniyle yakın gelecekte havzada su kıtlığı yaşanması olası görülmektedir. Modelleme çalışmaları; sistemin mevcut ve potansiyel sorunlarının analizi ve çözüm üretimi için, su kaynakları yönetimine bilimsel bir destek sağlamaktadır. Hidrolojik modeller sayesinde, sistemin su bütçesini oluşturan; yüzeysel akış, taban akışı, yeraltı suyu akımı, buharlaşma ve terleme miktarları hesaplanabilmektedir. Mevcut durum ve gelecek için; iklim, nüfus, arazi kullanımı, ürün deseni, sulama uygulamaları gibi faktörlerin muhtemel etkileri, çeşitli senaryolar aracılığıyla analiz edilebilmektedir. Bir sistem modellenirken; kurulacak modelin, mümkün olduğunca gerçeği temsil etmesi gerekmektedir. Bu açıdan, veri analizi aşaması oldukça önem taşımaktadır. Analiz aşamasında, çalışma alanının ölçeği göz önünde bulundurularak, verilerin etkin bir şekilde değerlendirilmesi gerekir. Bu kapsamda gerekli veriler, eğer mevcutsa ilgili resmi kuruluşlardan sağlanır; elde edilemeyen veriler için, web üzerinden, erişime açık yerel ve/veya küresel veri setlerinden yararlanılabilir. Verilerin entegrasyonunda; sayısal ve mekansal verilerin işlenmesinde, analiz edilmesi ve görselleştirilmesinde; coğrafi bilgi sistemi, sayısal hesaplama ve tablolama programları kullanılmaktadır. Bu çalışma kapsamında hidrolojik model olarak Stockholm Environment Institute (SEI) tarafından geliştirilen WEAP modeli seçilmiştir. WEAP; gelişmiş ve gelişmekte olan birçok ülkede yaygın bir kullanıma sahipken, Türkiye'de WEAP ile yürütülen oldukça az çalışma olduğu göze çarpmaktadır. Dolayısıyla, bu çalışma ülkemizde WEAP modelinin kullanıldığı ilk çalışmalardan biri olma özelliğini taşımaktadır. Çalışma alanı olarak seçilen Sakarya Havzası'nın yaklaşık %50'si tarım arazisinden oluşmaktadır. Ülkemizde halen yıllık su tüketiminde tarımsal sulama yaklaşık %74'lük oranla en büyük paya sahiptir. Bu nedenle, tarımsal faaliyetler ülkemizde su kaynakları yönetiminde önemli bir role sahip olduğundan, bitki merkezli bir modelin sistemin hidrolojik davranışlarını daha iyi yansıtacağı düşünülerek havzanın hidrolojik modellenmesinde WEAP modeli içerisinde bulunan PGM metodu kullanılmıştır. Su kaynakları yönetimine uygun bir altyapıya sahip WEAP-PGM, değişen atmosferik CO2 konsantrasyonunun ve sıcaklığın, bitki su kullanımı ve bitki büyümesi üzerindeki etkilerini hidrolojik sürece dâhil eder. Bu sayede iklim değişiklikleri çalışmaları kapsamında, küresel iklim değişikliğinin, bitki verimi ve bitki su tüketimine etkisi analiz edilebilmektedir. Veri analizi sonuçlarına göre; bitkisel ürünlerin mekânsal analizi sayesinde sulama ihtiyaçları öngörülerek, tarımsal üretimde bitki su tüketimi hesaplanabilecek ve ürün deseni değişimlerinin hidrolojik sisteme etkisi incelenerek suyun etkin kullanımı için ürün seçimi ile ilgili öneriler sunulabilecektir. Modelleme çalışmasında; Sakarya Havzası için yüksek çözünürlüklü bir hidrolojik modelin yapılandırılması amaçlanmış ve veri analizi/entegrasyonları yapılarak modelin kurulumu gerçekleştirilmiştir. Havzada yer alan; sulama alanları, su yapıları ve havzalararası su aktarımları da modelin kurulumu aşamasında tanımlanmış ve temin edilebilen veriler girilmiştir. Çalışma kapsamında; havzanın su bütçesi ortaya koyulmuş, havzanın çıkışında yer alan E12 A057 numaralı Adatepe istasyonunda, akış için yalnızca bir ön değerlendirme yapılmıştır. Ön değerlendirme sonuçlarına göre havzaya yılda ortalama 29993 milyon m3 yağış düşmekte, 5290 milyon m3'ü yüzeysel akışa dönüşmekte, 2070 milyon m3 su yer altı suyuna katılmaktadır. Yağışın, 10960 milyon m3'lük bölümü buharlaşma ile 11610 milyon m3'lük bölümü ise terleme ile atmosfere geri dönmektedir. T.C. Orman ve Su İşleri Bakanlığı Devlet Su İşleri Genel Müdürlüğü (DSİ) verilerine göre; Sakarya Havzası'nın yıllık ortalama yağış miktarı 524,7 mm olup, yıllık toplamda 33184 milyon m3 yağış düşmektedir. Sakarya Havzası, ortalama 6400 milyon m3 yıllık akış potansiyeline sahiptir. Yeraltı suyu potansiyeli ise yaklaşık 2197 milyon m3'tür. Elde edilen model sonuçlarının DSİ'nin uzun yıllar ortalama değerleri ile belirli derecede uyum gösterdiği görülmektedir. Bu tezin devamı niteliğindeki çalışmalarda; havza bütününde yapılacak kalibrasyon ve doğrulama işlemleri ile havzanın hidrolojik modeli tamamlanmış olacaktır. Bu sayede; su yönetimi kapsamında yapılacak çalışmalarda, su kaynaklarının; içme ve kullanma, sanayi, tarımsal sulama ve diğer sektörler arasında ne şekilde dağıtılabileceğine yönelik senaryo analizleri yapılabilecek ve etkin stratejiler geliştirilebilecektir. İklim değişikliğinin su kaynakları üzerindeki etkileri de bu senaryolar aracılığıyla analiz edilebilecektir.

Water, which is accepted as the source of life on Earth, is vital for all living things. In this respect, conscious use of water resources is of utmost importance. The rapid increase in world population, industrialization and agricultural activities has increased the use of water resources. Moreover, the potential effects of climate change on water quantity make the problem bigger. Thus, conscious use of water resources becomes more essential. The annual available water per capita in Turkey is 1519 m3, so it is accepted as a country that experiences water stress. In this context; studies conducted for preservation, development and sustainability of natural water resources, should have priority. Management of water resources at watershed scale in Turkey constitutes the basis for sustainable development of these resources. On the other hand, integrated watershed management is accepted as the main tool for the achievement of the European Union Water Framework Directive objectives. Sakarya Basin was selected as the study area. It is located in the northwest of the Anatolian Peninsula, which is among the 25 river basins of Turkey. The basin covers about 7% of Turkey with 58160 km2 drainage area. Since, it is located between two major provinces Ankara and İstanbul, the basin has high importance in terms of interbasin water transfers, economy, cultural activities and transportation. Sakarya Basin is accepted as a location that experiences water stress, because the annual available water per capita changes between 1000 - 1700 m3. Due to population growth, climate change and water management problems in the basin, it is possible to have water scarcity in the near future. Modeling studies provide scientific support for the management of water resources, for analyzing the problem and for developing strategies for current and potential problems. Hydrological models are used to calculate water budget components; such as surface runoff, subsurface flow, base flow, ground water flow, evaporation and transpiration. Possible effects of climate, population, land use, crop pattern, irrigation practices etc. can be analyzed with various scenarios developed for present and future time periods. When a system is modeled, it is necessary to represent the real world as much as possible with the developed model. Data analysis phase is of utmost importance for modelling. When analyzing data, considering the scale of the study area, data must be used effectively. During this step, required data can be obtained from the related government agencies, if they are available. If data are not available at the related government agencies local and/or global open access data sets can be downloaded via various web sites. Geographical information systems, numerical calculations and spreadsheet programs are used for integration of data, for numerical and spatial data processing, and for analysis and visualization. WEAP model, which is developed by Stockholm Environment Institute, was selected as the hydrological model to be used in this study. Although, WEAP model has been used widely in various developed and developing countries, there are only a few studies existing in Turkey. Thus, this study is among the pioneer studies in Turkey, where WEAP model is used. Approximately 50% of the selected study area consists of agricultural land. Almost 74% of annual water consumption in Turkey is for agricultural irrigation, which has the highest share among the sectors. Since agricultural activities have high importance in the management of water resources, it was thought that a plant-based model will better reflect the hydrological behavior of the system; thus, PGM method of WEAP model was used for the hydrological modelling of the basin. WEAP-PGM model has an appropriate structure for water resources management, it includes the effect of changing atmospheric CO2 concentration and temperature on plant water consumption and plant growth, in the hydrological process. Thus, effect of global climate change on plant efficiency and plant water consumption can be analyzed. By using the data analysis results; irrigation demand can be predicted with the spatial analysis of crops. Water consumption for agricultural production can be calculated; and the effect crop pattern changes on the hydrological system can be analyzed. After these analysis, suggestions can be made for the selection of products for efficient water use. The main objective of this study is to structure a high resolution hydrological model Sakarya Basin. Data analysis/integration has been done for setting up the model. Irrigated land, hydraulic structures and interbasin transfers in the basin were defined to the model and obtained data were entered. Water budget of the basin was calculated within the study, and a preliminary flow assessment was conducted for E12 A057, Adatepe stream gauging station. Drainage areas of the basin were determined by using ArcSWAT software. While setting up the hydrological model it was aimed to define a drainage basin for each water body in the basin. Finally, 379 sub basins have been defined for Sakarya Basin. Land use, crop pattern and soil characteristics data of the basin were compiled and organized in order to define the Hydrological Response Units (HRUs). ArcMap, MS Excel and MATLAB programs were used for defining site specific data for each HRU category. 1:25000 scaled National Soil Database produced at provincial level were obtained from Turkish Republic Ministry of Food, Agriculture and Livestock. ISRIC soil data set generated in Soil Grid 1 km Project were downloaded from its web site. 30 raster data were generated, which includes the average silt percentage, sand percentage, bulk density and coarse fragment characteristics, for six layers for each great soil group – depth combination. Raster data were overlaid with great soil group – depth combination areas of the national database, and average values were calculated for each of it. Average pixel values of ISRIC data, corresponding to each spatial area of Great Soil Group – depth combination elements were calculated, and physical and hydraulic characteristics of soil were analyzed for each combination group. Pedotransfer functions were used to determine the soil – water relations. In order to determine the spatial distribution of land use, crop pattern and planted land TÜİK Crop Production Database and CORINE Land Cover Project spatial data were integrated. National and global database, which is publicly available and can be accessed through internet, were utilized for this purpose. Spatial attributes were added to TÜİK database with this integration. As a result, the distribution of crops was calculated in an agriculture area (e.g. 70% wheat, 10% barley, 40% corn); instead of a general classification like "Agricultural land". An alternative solution has been presented, particularly for crop pattern analysis conducted within hydrological and agricultural studies in Turkey. According to the analysis conducted after CORINE - TÜİK data integration, the distribution is of agricultural land in Sakarya Basin in 2015 is as follows: 76% is non-irrigated agriculture, 22% is irrigated agriculture, and 3% is garden. Wheat has the highest share with 32% in non – irrigated agriculture, whereas barley is the second one with 14.4% share, and 24.3% of agricultural land is fallowed. Sunflower, beet, pea, alfalfa and corn appears to have high share in irrigated agriculture. The methodology developed for 2015 can also be applied to previous years. It is possible to identify and compare, crop pattern of previous years with this methodology. Stand type map of the study area was integrated CORINE data. According to analysis results of integration; 74.58% is pine, 14.92% is oak, 10.26% is maple and 0.23% is poplar trees. After the compilation and integration of all required data, the hydrological model was run. According to the model results, annual average precipitation was estimated as 29993 million m3. 5290 million m3 of precipitation is converted to runoff, and 2070 million m3 of precipitation infiltrates into groundwater. 11610 million m3 and 10960 million m3 of precipitation goes back to atmosphere through transpiration and evaporation, respectively. According to DSİ data, annual average rainfall is 524.7 mm, thus, annual precipitation in Sakarya Basin is 33183.6 million m3. Annual average flow in basin is 6400 million m3, and the groundwater potential is 2197.1 million m3, which is in agreement with model results. Calibration and validation of the model should be completed in the future studies. When calibration and validation step is completed it will be possible to develop effective strategies and scenarios for the management of water resources, such as water allocation for sectors like drinking – consumption, industry, irrigation and other sectors. Effects of climate change on water resources can be analysed within these scenarios.
Structuring The High Resolution Hydrological Model Of Sakarya Basin
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Yüzeysel Su Kaynakları; Hidrolojik Modelleme; Havza Modellemesi; Bilgisayar Destekli Modelleme; Yüzey Hidrolojisi; Hidrolojik Modeller; Bitki Büyüme Modeli; Su Kaynakları Yönetimi; Veri Analizi; Corıne Arazi Örtüsü; Tüik; Isrıc; Ürün Deseni; Toprak Yapısı; İklim Değişikliği; Küresel Isınma; Hidrolojik İşlem Birimleri; Sakarya Havzası; Weap; Swat; Surface Water Resources; Hydrological Modelling; Basin Modelling; Computer Aided Modelling; Surface Hydrology; Hydrologic Modelsplant Growth Model; Water Resources Management; Data Analysis; Corine Land Cover; Turkish Statistical Institute; Isric; Crop Pattern Soil Stucture; Climate Change; Global Warming; Hydrologic Response Units; Sakarya Basin; Weap; Swat